MINYAK ATSIRI BERBAHAN KULIT JERUK DAN BUNGA KENANGA SEBAGAI AROMA TERAPI PADA MATA KULIAH PERAWATAN BADAN - Iut Nuraini; Fitria Hansyah Fatmasari; Ria Andriani Mukti (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2023)
Aromatherapy is a material used by students in body care courses to improve fitness and is an important aspect so that the activities carried out can be optimal, but students often complain that the use of aramotherapy is expensive and wasteful. This needs efforts to overcome it with non-pharmacological therapies such as aromatherapy of essential oils made from orange peel and ylang flowers. The purpose of this study was to analyze the use of essential oil aromatherapy made from orange peel and ylang flowers from the aspect of cost efficiency in PVKK students, Faculty of Engineering, PGRI Adi Buana University, Surabaya. The method used in this study is making aromatherapy with organoleptic tests and conducting analysis conclusions. The results of research that has been carried out experiments and tested that the essential oils of orange peel and ylang flowers can be used as aromatherapy. The conclusion is that the essential oils from orange peel and ylang flowers have a good aroma, and are very affordable from an economical point of view when compared to other aromatherapy treatments